Ob izročilu pravne znanosti - Pavčnik, Marijan (Pravnik, 2023)
The contribution is the author’s commemorative address marking the 103rd anniversary of the University of Ljubljana Faculty of Law. The author leaned on the tradition of jurisprudence, while being aware that we should not cling to tradition convulsively and stand still. We must start from tradition, correct it and supplement it. If necessary, due to new insights and new circumstances, we must also transcend it and diverge from traditional pathways. Central to the contribution is the idea that constitution, laws and other normative acts cannot be implemented automatically. It is always a matter of first understan- ding these acts and only then deciding how to implement them in concrete cases. Behind every responsible legal decision-making is the knowledge that even minor value nuances and new minor factual circumstances can influence our perception of what the elements of legal reasoning mean and how they in- terrelate. If this is correct, interpretation and justification (argumentation) are necessary and constant companions of legal decision-making. The meaning of legal understanding is, volens nolens, shared. It can only be achieved and dee- pened through a collaborative effort between the theory (philosophy) of law and individual positive legal sciences.
Keywords: analognost prava; delitev oblasti; narava prava; pravna država; pravna znanost; razlagalnost prava; študij prava